2017
DOI: 10.1177/0305735617707354
|View full text |Cite
|
Sign up to set email alerts
|

Music listening as self-enhancement: Effects of empowering music on momentary explicit and implicit self-esteem

Abstract: In everyday life people use music to adjust their levels of arousal, to regulate their mood and emotions, and to cope with previous experiences, indicating that music plays an important role for everyday wellbeing. While the relationship between music and emotions has received considerable interest in past decades, little is known about the self-esteem boosting function of empowering music. In the present study, we investigated the relationship of music listening and self-esteem, by examining how momentary exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 82 publications
0
14
1
Order By: Relevance
“…Although there is evidence in favor of a positive effect of music listening on self-esteem (Brown and Mankowski, 1993 ; Elvers et al, 2017 ), this study found neither a direct effect of motivational music on the enhancement of state self-esteem nor a reduction of cognitive and bodily anxiety. Since mean gain scores for state self-esteem were negative across conditions, the ball-throwing task itself seems to have had a negative impact on self-evaluative cognitions.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Although there is evidence in favor of a positive effect of music listening on self-esteem (Brown and Mankowski, 1993 ; Elvers et al, 2017 ), this study found neither a direct effect of motivational music on the enhancement of state self-esteem nor a reduction of cognitive and bodily anxiety. Since mean gain scores for state self-esteem were negative across conditions, the ball-throwing task itself seems to have had a negative impact on self-evaluative cognitions.…”
Section: Discussioncontrasting
confidence: 82%
“…More specifically, this account suggests that listening to music fulfills self-enhancement needs, providing listeners with enhanced self-esteem, optimism, and self-worth. Initial experimental evidence suggests that listening to powerful music activates power-related cognition and behavior (Hsu et al, 2014 ) and that listening to empowering music enhances momentary self-esteem (Elvers et al, 2017 ). Following from this initial evidence, we assume that motivational music also exerts a positive influence on self-evaluative cognition and subsequent behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within these lifespan perspectives, research into music's contribution to health and well-being provides evidence of physical and psychological impacts (MacDonald et al, 2013;Fancourt and Finn, 2019;van den Elzen et al, 2019). Benefits are also reported in terms of young people's educational outcomes (Guhn et al, 2019), and successful musical activity can enhance an individual's sense of social inclusion (Welch et al, 2014) and social cohesion (Elvers et al, 2017).…”
Section: The Impact Of Music On Human Development and Well-beingmentioning
confidence: 99%
“…A number of studies have attempted to show how music carries human affective states [2] and boosts mood and self-confidence [3][4][5]. Sometimes, this emotional effect is counterintuitive, as even sad music can evoke pleasure and comfort in listeners [6,7].…”
Section: Introductionmentioning
confidence: 99%